2015
DOI: 10.1126/science.aaa4170
|View full text |Cite
|
Sign up to set email alerts
|

Quantum versus classical annealing of Ising spin glasses

Abstract: Quantum annealers use quantum fluctuations to escape local minima and find low-energy configurations of a physical system. Strong evidence for superiority of quantum annealing (QA) has come from comparing QA implemented through quantum Monte Carlo (QMC) simulations to classical annealing. Motivated by recent experiments, we revisit the question of when quantum speedup may be expected. Although a better scaling is seen for QA in two-dimensional Ising spin glasses, this advantage is due to time discretization ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
232
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(234 citation statements)
references
References 29 publications
1
232
1
Order By: Relevance
“…Heim et al [7] among others have shown that qmc methods outperform classical sa in several cases. In other situations Battaglia et al [8] showed that sa can perform better than qmc.…”
Section: Introduction a Backgroundmentioning
confidence: 99%
“…Heim et al [7] among others have shown that qmc methods outperform classical sa in several cases. In other situations Battaglia et al [8] showed that sa can perform better than qmc.…”
Section: Introduction a Backgroundmentioning
confidence: 99%
“…It is often stated that quantum annealing (QA) [5][6][7][8][9] uses tunneling instead of thermal excitations to escape from local minima, which can be advantageous in systems with tall but thin barriers that are easier to tunnel through than to thermally climb over [4,9,10]. It is with this potential tunneling-induced advantage over classical annealing that QA and the quantum adiabatic algorithm [11] were proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The tunneling from the metastable well has to be at energy and spin values, E and k, at which a state exists in the ground state well, i.e., E ≥ min fE R ðkÞg, which is not always satisfied in the system with large entropy of states; i.e., F L < F R does not necessarily imply E L < E R . Equation (17) has a solution in a range of energies E such that T min ≤ TðEÞ < ∞ (see inset in Fig. 3, left).…”
Section: Quantum Tunnelingmentioning
confidence: 99%
“…For β < T min , there are no solutions to Eq. (17), and therefore, the optimal energy is at the edge of the interval E ¼ Uðq max Þ − Uðq min Þ corresponding to the height of the barrier. In other words, in this regime, the over-the-barrier escape process dominates, with β ∼ T min being the point of a quantum-to-classical phase transition.…”
Section: Quantum Tunnelingmentioning
confidence: 99%
See 1 more Smart Citation